1988
DOI: 10.1002/j.1460-2075.1988.tb03161.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex alternative splicing of acetylcholinesterase transcripts in Torpedo electric organ; primary structure of the precursor of the glycolipid-anchored dimeric form.

Abstract: In this paper, we show the existence of alternative splicing in the 3′ region of the coding sequence of Torpedo acetylcholinesterase (AChE). We describe two cDNA structures which both diverge from the previously described coding sequence of the catalytic subunit of asymmetric (A) forms (Schumacher et al., 1986; Sikorav et al., 1987). They both contain a coding sequence followed by a non‐coding sequence and a poly(A) stretch. Both of these structures were shown to exist in poly(A)+ RNAs, by S1 mapping experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(57 citation statements)
references
References 52 publications
4
53
0
Order By: Relevance
“…Anchoring by a KDEL peptide sequence receptor as described for the liver microsomal carboxylic ester hydrolase 1361 or by a stop-translocation signal 1371 can also be ruled out as no such sequences were present on any BSDL [S, 9, 30, 381. The possible involvement of a (Ose),,GroPIns tail as described for acetylcholinesterase [ 31 ] which is structurally related to BSDL [30] or the association with a (Ose),,GroPlnstailed protein, can also be ruled out. A Golgi retention signal [391 is also not present on any known BSDL sequence 18.…”
Section: Discussionmentioning
confidence: 99%
“…Anchoring by a KDEL peptide sequence receptor as described for the liver microsomal carboxylic ester hydrolase 1361 or by a stop-translocation signal 1371 can also be ruled out as no such sequences were present on any BSDL [S, 9, 30, 381. The possible involvement of a (Ose),,GroPIns tail as described for acetylcholinesterase [ 31 ] which is structurally related to BSDL [30] or the association with a (Ose),,GroPlnstailed protein, can also be ruled out. A Golgi retention signal [391 is also not present on any known BSDL sequence 18.…”
Section: Discussionmentioning
confidence: 99%
“…This was first established for different forms of the variant surface glycoprotein of T. brucei (7,32), the mammalian antigen Thy-1 (60,68), and placental alkaline phosphatase (51,53). To date, processing of the C-terminal hydrophobic domain has been demonstrated for more than a dozen distinct GPI-anchored proteins (15,22,27,29,35,36,47,62,65).…”
Section: Discussionmentioning
confidence: 99%
“…This particular feature seems to be important in the mechanism of anchor addition. In all cases studied so far, addition of the GPI anchor involves the removal of 17 to 31 residues from the C terminus of a larger precursor (7,15,22,27,29,32,35,36,47,51,53,60,62,65,68). Since processing rapidly follows protein synthesis (2, 18, 24), it is believed that the GPI moiety is preassembled and transferred en bloc to the protein in the endoplasmic reticulum.…”
mentioning
confidence: 99%
“…with noncatalytic subunits, hydrodynamic properties, and sites of subcellular localization (17). One level at which this diversity is controlled appears to be alternative splicing of 3Ј exons (11,15,28). Transfections of AChE-coding sequences into mammalian cells indicated that alternative splicing alone could account for these multiple molecular forms of AChE (5,12,14,16).…”
Section: Bmentioning
confidence: 99%